2009
DOI: 10.1016/j.bpj.2009.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Oxazole Yellow Dyes with DNA Studied with Hybrid Optical Tweezers and Fluorescence Microscopy

Abstract: We have integrated single molecule fluorescence microscopy imaging into an optical tweezers set-up and studied the force extension behavior of individual DNA molecules in the presence of various YOYO-1 and YO-PRO-1 concentrations. The fluorescence modality was used to record fluorescent images during the stretching and relaxation cycle. Force extension curves recorded in the presence of either dye did not show the overstretching transition that is characteristic for bare DNA. Using the modified wormlike chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
105
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 27 publications
19
105
5
Order By: Relevance
“…First, we showed that at equilibrium SYTOX green occupies a minimum of ~3.5 bp. These values are in agreement with those reported for other monointercalators, such as ethidium bromide (~2.4-3 bp) (Vladescu et al 2007), and YO-1 (~4 bp) (Murade et al 2009), or for bis-intercalators such as YOYO-1 (3.2 bp) (Günther et al 2010) or triostin A (4 bp) (Kleimann et al 2009). Secondly, we showed that upon intercalation of SYTOX green, the extension of the DNA molecule increases by ~43 %, which is consistent with fractional elongations reported for other intercalators (17-47 %) (Chaurasiya et al 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, we showed that at equilibrium SYTOX green occupies a minimum of ~3.5 bp. These values are in agreement with those reported for other monointercalators, such as ethidium bromide (~2.4-3 bp) (Vladescu et al 2007), and YO-1 (~4 bp) (Murade et al 2009), or for bis-intercalators such as YOYO-1 (3.2 bp) (Günther et al 2010) or triostin A (4 bp) (Kleimann et al 2009). Secondly, we showed that upon intercalation of SYTOX green, the extension of the DNA molecule increases by ~43 %, which is consistent with fractional elongations reported for other intercalators (17-47 %) (Chaurasiya et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…A second and alternative hypothesis for the reduced rate of the second step is that only dye molecules having a favorable orientation (i.e., parallel to the DNA bases) can bind stably and therefore only a fraction of the total collisions of SYTOX green with DNA results in intercalated/fluorescent complexes. Binding mechanisms involving two states were proposed in the past for bis-intercalators (Murade et al 2009), and more recently for mono-intercalators (YO-1) (Paik and Perkins 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A further debate was related to how YOYO-1 influences the bending stiffness or softening of the biopolymer. Quake et al reported a 32% persistence-length increase of DNA with optical tweezers (3), whereas two other groups have measured reduction of 70% with the same methodology (4,5). Shi et al have used entropic force microscopy and observed a reduction of 9% of the persistence length (7).…”
Section: Introductionmentioning
confidence: 99%
“…Molecules of dyes can label compounds by a covalent bonding using an active group (-SH, -COOH, -NH 2 ) or might be inserted into the double-helix structure of DNA by affinity, as in the case of thiazole orange, oxazole yellow and their dimers [13,14]. Antibodies (their size is about 12 nm) endowed with fluorescent dyes (e.g., Alexa Fluor 488 λEm=525 nm and Texas Red λEm=609 nm) [15][16][17] were used in the development of a wide range of effective targeted therapies [18][19][20][21][22] but they create clustering artifacts due to limited antibody penetration, which have an impact on insufficient labeling density.…”
Section: Fluorescent Small Molecules As Cell-type-specific Imaging Prmentioning
confidence: 99%